La ética del contador público ecuatoriano y su desempeño profesional - Chiluisa Moreno, Rocío Maribel (2019)
This project entitled "The Ethics of the Ecuadorian Public Accountant and its professional performance" is aimed at studying the conduct of the accountant where the main problem was established as the breach of ethical standards in the performance of their duties, seeking to determine How does it fulfill its ethical responsibility to society ”, which is why the research project aimed to determine the incidence of ethics in the professional performance of accountants belonging to the Municipal GADs of the Province of Cotopaxi. For the development of the project, the quantitative methodology was used since it allowed to interpret results and define them easily through the application of instruments, such as the survey that was carried out to 21 professionals, among them the Chief Financial Officers, Accountants and Accounting Assistants. Among the main results is the relationship to non-compliance with the Accountant's Code of Ethics, the presentation of false and / or late financial information and corruption, are the most prevalent factors, followed by the dissemination of accounting information without authorization from its managers, outdated regulations in force, confusion regarding the basic principles of the CECE, this action influences the social environment, since the ethics and moral values that are part of the professional's preparation are not fully used, it can be indicate that accounting professionals, not knowing exactly the Code of Ethics of the Ecuadorian Accountant, may have difficulties in the development of their functions since when applying accounting ethics in the exercise of their activities, it affects the information presented within of the economic activities of the organizations, resulting in fraud, which would cause loss of d but that would harm the municipal budget, as well as economic problems within the GAD.